Tagged Halloysite Nanotubes as a Carrier for Intercellular Delivery in Brain Microvascular Endothelium - Saleh, Mahdi Yar; Prajapati, Neela; DeCoster, Mark A.; Lvov, Yuri (Frontiers in Bioengineering and Biotechnology, 2020)
Neurological disorders that are characterized by unpredictable seizures affect people of all ages. We proposed the use of nanocarriers such as halloysite nanotubes to penetrate the blood brain barrier and effectively deliver the payload over an extended time period. These 50-nm diameter tubes are a natural biocompatible nanomaterial available in large quantities. We proved a prolonged gradual drug delivery mechanism by the nanotube encapsulating rhodamine isothiocyanate and then ionomycin into brain microvascular endothelial cells. Through delayed diffusion, the nanotubes effectively delivered the drug to the primary brain microvascular endothelial cells without killing them, by binding and penetration in time periods of 1 hour to 24 hours.